Analisis Penggunaan Media Pembelajaran Schoology pada Matakuliah Praktikum Biologi Lingkungan Terhadap Hasil Belajar Mahasiswa di Era Pandemi Covid-19 - Ima Aryani*; Purwo Adi Nugroho (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
Learning must continue to run in harmony even though it is still in a state of the Covid-19 Pandemic. The outbreak that originated in Wuhan, China at the end of 2019 has not yet subsided, making all universities rack their brains to continue to provide educational services during the pandemic. One of them was carried out in the Biology Education study program at Muhammadiyah University of Surakarta, namely by implementing online learning using the Schoology application. Practical courses do not have to be fully implemented offline but can also be applied using online methods with clear implementation instructions from the lecturer. This study aims to analyze the effectiveness of the use of Schoology on the learning outcomes of semester 1 students in the Environmental Biology practicum course which is carried out online due to the Covid-19 pandemic still not abating. The type of research used is qualitative research with a case study design, where student learning outcomes are taken from the results of student work carried out and reported to Schoology. Determination in taking research subjects using purposive sampling technique. The data collection technique is in the form of student assignments, while the validity of the data uses triangulation of data sources in the form of archives, written documents, pictures, and photos. The data analysis technique is using the following methods: 1) Grouping data based on learning outcomes, 2) presenting in the form of narrative text, pictures, and tables, and 3) concluding from the whole learning process. From the research process, it was found that the average student learning outcomes were 78.35% from four times the implementation of the lecture process using Schoology